PERBEDAAN WAKTU PERALIHAN PAKAN PADA PEMELIHARAAN POST LARVA IKAN GABUS (Channa striata) - Tara Suprayogi; ade dwi sasanti; yulisman . (Universitas Sriwijaya, 2016)
ABSTRACT Snakehead culture still has problem in production stage, especially at larvae phase because of high mortality after yolk sac finish period. The aim of this research is to determine the effect of feeding time different to growth and survival rate of Channa striata post larvae. The research was conduct on June until July 2015 in Laboratorium Dasar Perikanan, Department of Budidaya Perairan, Faculty of Agriculture, Sriwijaya University. The research methods used Completely Randomized Design (CRD) with five treatments and three replications, method of changing the feed includes the naupli Artemia sp., Daphnia sp., and silk worm. The parameters of this research are growth of length, weight, survival rate, and water quality. The result of this research showed that feeding snakehead larvae by nauplii Artemia sp. at larvae age 4 – 13 days, Daphnia sp. at larvae age 16 – 21 days and silk worm at larvae age 24 – 33 days was the best time to result better of Channa stirata spesific growth and survival rate of. Water quality during the research were temperature 26.9 – 28.6 oC, pH 6.3 – 6.8, dissolved oxygen 3.29 – 4.31 mg.L-1,and ammonia 0.09 – 0.43 mg.L-1. Key words : nauplii Artemia sp, Daphnia sp, silk worm, Channa striata